Do the stars align? Distribution of high-quality ratings of healthcare sectors across US markets. Issue 4 (12th September 2017) - Figueroa, Jose; Feyman, Yevgeniy; Blumenthal, Daniel; Jha, Ashish
Abstract : Background: The US government created five-star rating systems to evaluate hospital, nursing homes, home health agency and dialysis centre quality. The degree to which quality is a property of organisations versus geographical markets is unclear. Objectives: To determine whether high-quality healthcare service sectors are clustered within US healthcare markets. Design: Using data from the Centers for Medicare and Medicaid Services' Hospital, Dialysis, Nursing Home and Home Health Compare databases, we calculated the mean star ratings of four healthcare sectors in 304 US hospital referral regions (HRRs). For each sector, we ranked HRRs into terciles by mean star rating. Within each HRR, we assessed concordance of tercile rank across sectors using a multirater kappa. Using t-tests, we compared characteristics of HRRs with three to four top-ranked sectors, one to two top-ranked sectors and zero top-ranked sectors. Results: Six HRRs (2.0% of HRRs) had four top-ranked healthcare sectors, 38 (12.5%) had three top-ranked health sectors, 71 (23.4%) had two top-ranked sectors, 111 (36.5%) had one top-ranked sector and 78 (25.7%) HRRs had no top-ranked sectors. A multirater kappa across all sectors showed poor to slight agreement (K=0.055). Compared with HRRs with zero top-ranked sectors, those with three to four top-ranked sectors had higher median incomes, fewer black residents, lower mortality rates and were less impoverished. Results were similar for HRRs with one to two top-ranked sectors. Conclusions: Few US healthcare markets exhibit high-quality performance across four distinct healthcare service sectors, suggesting that high-quality care in one sector may not be dependent on or improve care quality in other sectors. Policies that promote accountability for quality across sectors (eg, bundled payments and shared quality metrics) may be needed to systematically improve quality across sectors.